Uruguayan Mural Painting heritage: Patrimonial activation, scientific catalogation and its socio historic repercussion - María Jesús Guirado; Andrea Lage Hermida; Virginia Santamarina Campos; Dolores Julia Yusa Marco; Mercedes Sánchez Pons (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This poster shows part of the results of the investigation for the project “Planning and establishing an inclusive cultural policy: Uruguayan Contemporary mural Art as a tool for sustainable heritage”. Four mural paintings by artists Eloy Boschi, Miguel Ángel Zelayeta, Demetrio Uruchúa y Esteban Garino were analyzed by means of Light Microscopy (LM) and Scanning Electron Microscopy (SEM) to obtain more information about the technical and historic influences of these particular works of art.